MULTICHANNEL STRATEGY – THE DOMINANT APPROACH IN MODERN RETAILING - Stojković, Dragan; Lovreta, Stipe; Bogetić, Zoran (Economic Annals, 2016)
The purpose of this paper is to thoroughly analyse the concept of multichannel strategy, focussing on retail, to enable the academic community and marketers to better understand its advantages and disadvantages. This paper presents a comprehensive literature review and financial data analysis. The authors have analysed the financial data of 88 retail companies in the 2007 to 2014 period, and have proven that the importance of multichannel strategy has grown with the emergence of e-commerce. The main hypothesis is that the multichannel concept dominates modern marketing channels because it is widely accepted and provides superior financial performance. Multichannel retailing is definitely a winning concept, if adequately implemented. However, wrongly implemented it can negatively influence business performance.